Spatiotemporal variations of the oxycline and its response to subduction events in the Arabian Sea - Zhou, Yesheng; Chen, Shuangling; Ma, Wentao; Xi, Jingyuan; Zhang, Zhiwei; Xing, Xiaogang (Frontiers in Marine Science, 2023)
The Arabian Sea is a significant hypoxic region in world’s oceans, characterized by the most extensive oxygen minimum zones (OMZs). Both physical and biological processes can alter the vertical and horizontal distribution of dissolved oxygen within the upper ocean and affect the spatial and temporal distribution of hypoxia within the OMZ. To identify the key physical and biological factors influencing the boundaries of oxycline, we analyzed an extensive dataset collected from the biogeochemical-Argo (BGC-Argo) floats during the period of 2013–2022. In particular, we investigated the impact of physical subduction events on the oxycline. Our results shows that the upper boundary of the oxycline deepened in summer and winter, and seemed to be controlled by the mixed layer depth. In contrast, it was shallower during spring and autumn, mainly regulated by the deep chlorophyll maximum. The lower boundary of the oxycline in the western Arabian Sea was predominantly controlled by regional upwelling and downwelling, as well as Rossby waves in the eastern Arabian Sea. Subduction patches originated from the Arabian Sea High Salinity Water (ASHSW) were observed from the BGC-Argo data, which were found to deepen the lower boundary of the oxycline, and increase the oxygen inventory within the oxycline by 8.3%, leading to a partial decrease in hypoxia levels.